0
$\begingroup$

Prove that $\exp\left(\frac{p}{q} x\right) = \exp(x)^\frac{p}{q}$, considering $\displaystyle\exp(x) =\sum_{n=0}^\infty\frac{x^n}{n!}$.

I must use only the definition of exp(x) being a power series to show that $\exp(\frac{p}{q} \cdot x)$. I already have that $\exp(n\cdot x) = \exp(x)^n$ for $n \in \mathbb{N}$, which I used induction on $n$ to prove.

I wanted to consider the case p=1, then I tried to make an induction on $q$ but it wasn't useful. How could I prove it?

$\endgroup$
  • $\begingroup$ From $\exp(nx)=\exp(x)^n$, you can prove that $\exp\left(\frac{x}{q}\right)=\exp(x)^{\frac1q}$. $\endgroup$ – Batominovski Jan 22 '17 at 16:26
2
$\begingroup$

If you already know that $\exp(nx)=\exp(x)^n$, then you can set $y=x/q$, so $$ \exp(py)=\exp(y)^p $$ On the other hand, $$ \exp(x)=\exp(qy)=\exp(y)^q $$

so $$\exp(y)=\exp(x)^{1/q}$$

This works for $p,q>0$. The case $p<0$ follows easily from $\exp(-x)=\exp(x)^{-1}$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.